EVALUATION OF MOTOR AND COGNITIVE DEVELOPMENT OF CHILDREN WITH MENTAL RETARDATION (Fiep Bulletin - online, 2014)
The aim of the study was to evaluate the motor and cognitive development of children with mental retardation. For both, were assessed 32 children from 6 to 11 years, belonging at 09 special schools in the region of Florianópolis/SC/Brazil. For the assessment of the motor development was used to Scale Development Motor-EDM (Rosa Neto, 2002), which assesses the fine motricity, global motricity, balance, scheme body, spatial organization, timing organization (language) and laterality. Through this scale, it is possible to obtain the Quotient General Motor (QMG) for each child, which is classified in 7 levels "much higher", "top", "normal high", "normal average," "normal low", " lower" and " much lower ". For the evaluation of cognitive development used to the Wechsler Intelligence Scale for Children- WISC-III (Wechsler, 2002), through tests of "cubes" and "vocabulary", and to get Quotient of Intelligence (QI) estimated for each child. The results found show that the motor development of children with mental retardation is "much lower" and the cognitive development is "deficit". Found is positive correlation between motor development and cognitive development (r=0.6), suggesting that by evaluating motor development can detect cognitive changes.
Keywords: mental retardation; motor development; cognitive development